Association of the 12-Gene Breast DCIS Score® Assay With Local Recurrence in Patients With Ductal Carcinoma In Situ Treated on Accelerated Partial Breast Radiotherapy Protocols - Leonard, Charles E.; Tole, Shannon P.; Turner, Michelle P.; Bennett, John P.; Howell, Kathryn T.; Carter, Dennis L. (Frontiers in Oncology, 2021)
Background: The following analysis explores clinicopathologic factors and the 12-gene Breast DCIS Score test result in order to better define an appropriate DCIS (ductal carcinoma in situ) population eligible for APBI (accelerated partial breast radiotherapy). Methods: This exploratory analysis aimed to retrospectively measure the association between the 12-gene Oncotype DX Breast DCIS Score® assay (Redwood City, CA) and relevant clinicopathologic factors with locoregional recurrence in a pooled cohort of women treated with local excision and APBI on prospective phase II (NCT01185145) and phase III (NCT01185132) clinical trials. Univariable Cox proportional hazards regression was used to determine whether there was an association between local recurrence and DCIS Score result risk group (≥ 39 vs < 39) and clinicopathologic factors. Results: This analysis included 104 evaluable patients (n=18 from NCT01185145 and n=86 from NCT01185132). The median age was 60 years (range: 40-79). Seventy-nine percent of patients were postmenopausal. The median span of DCIS was 10 mm (range 2-45 mm). Two-thirds of the cohort presented with necrosis (71%). The distribution of DCIS Score® results ranged from 0 to 82, with 69% of patients having a DCIS Score result < 39. The median follow-up time was 8.2 years in NCT01185145 versus 3.0 years in NCT01185132. There were 6 local ipsilateral breast recurrences. DCIS Score result was significantly associated with local recurrence in univariable modeling, hazard ratio=10.3 (95% CI 1.7, 198.4); p=0.010. None of the clinicopathologic characteristics resulted in any significant association with locoregional recurrence. Conclusion: The Breast DCIS Score assay demonstrated risk stratification in this cohort of patients treated with local excision and APBI pooled from two clinical trials. These results are consistent with those recently published utilizing whole breast radiotherapy. Due to the small number of local recurrence events and limited follow-up time, further investigations are needed to confirm findings.